Dietary phenylalanine level could improve growth performance, glucose metabolism and insulin and mTOR signaling pathways of juvenile swimming crabs, Portunus trituberculatus - Chen Guo; Xiangsheng Zhang; Shichao Xie; Jiaxiang Luo; Tingting Zhu; Yuhang Yang; Xiangkai Li; Chaokai Huang; Yunfei Dang; Qicun Zhou; Min Jin (Aquaculture Reports, 2022)
An 8-week feeding trial was conducted to determine the optimal dietary phenylalanine requirement of juvenile swimming crab (Portunus trituberculatus). Six experimental diets (45.0% crude protein and 8.0% crude lipid) were formulated to contain 0.89%, 1.15%, 1.41%, 1.64%, 1.90% and 2.18% phenylalanine, respectively. Each diet was randomly divided into triplicate groups with 30 juvenile swimming crabs (initial weight 22.87 ± 0.03 g). The highest percent weight gain (PWG) and feed efficiency (FE) were presented in crabs fed with 1.64% phenylalanine diet, and the lowest PWG and FE were observed in crabs fed diet with 0.89% phenylalanine (P < 0.05), while no significant difference was presented in survival among all treatments (P > 0.05). Crabs fed the diet containing 0.89% phenylalanine had the lowest content of crude lipid in hepatopancreas among all treatments (P < 0.05). Hematological parameters related to glucose and lipids metabolism and enzyme activities involved in glycolysis and gluconeogenesis were significantly affected by dietary phenylalanine levels (P < 0.05). The contents of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), n-6 polyunsaturated fatty acids (n-6 PUFAs) and n-3 polyunsaturated fatty acids (n-3 PUFAs) in the hepatopancreas were notably affected by the dietary phenylalanine levels (P < 0.05). The enzyme activities related to glycolysis, gluconeogenesis and glycogen content in hepatopancreas were significantly influenced by dietary phenylalanine levels (P < 0.05). The mRNA levels of genes related to glycolysis and gluconeogenesis in the hepatopancreas were significantly affected by dietary phenylalanine levels (P < 0.05). Moreover, the insulin and mammalian target of rapamycin (mTOR) signaling pathway were notably activated by dietary phenylalanine levels (P < 0.05). Based on two slope broken-line regression analysis of PWG against the dietary phenylalanine levels, the optimal dietary phenylalanine requirement was estimated to be 1.60% dry matter (3.55% dietary protein) for juvenile swimming crab.